Dravet Syndrome -A case report from Aseer, Saudi Arabia (Bangladesh Journal of Medical Science, 2020)
Dravet syndrome (DS) is an epileptic encephalopathy that presents with protracted seizures in infancy, associated with fever, and frequently categorized as febrile seizure at first presentation. In the second year, myoclonia, atypical absence and complex partial seizures develop. The correct diagnosis of DS and appropriate follow-up are delayed until after appearance of signs of developmental regression in the second year of life. Timely detection and diagnosis of DS followed by management with suitable anticonvulsants and treatment plan may reduce the seizure burden and improve long-term developmental outcome. We present a case of 2 years old female with recurrent attacks of generalized tonic colonic convulsion after 1st febrile convulsion diagnosed as Dravet syndrome. The diagnosis was based on history and gene study (SCN1A).Bangladesh Journal of Medical Science Vol.19(2) 2020 p.315-318